2013
DOI: 10.5812/numonthly.4934
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Serum Cystatin C and Creatinine or Dialysis Adequacy in Patients on Chronic Maintenance Hemodialysis

Abstract: BackgroundGlomerular filtration rate (GFR) is widely estimated by serum creatinine based equations such as Cockcroft-Gault (CG) standardized for body surface, and an abbreviated formula derived from MDRD (modification of diet in renal disease) study. However, some studies suggested that creatinine based estimation of GFR formula can be replaced by cystatin C based formula.ObjectivesThe aim of this study was to determine whether cystatin C based equation could be used as an indicator for renal function in hemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…We studied a larger number of patients and compared GFR in normal and different stages of CKD. Our study also confirmed the previous studies with more solid data in wider range of kidney function [14]. However, Hejes, et al insisted that cystatin C-based GFR formula was more accurate than creatininebased GFR formula in patients with GFR<60cc/min/m 2 [11].…”
Section: Discussionsupporting
confidence: 90%
“…We studied a larger number of patients and compared GFR in normal and different stages of CKD. Our study also confirmed the previous studies with more solid data in wider range of kidney function [14]. However, Hejes, et al insisted that cystatin C-based GFR formula was more accurate than creatininebased GFR formula in patients with GFR<60cc/min/m 2 [11].…”
Section: Discussionsupporting
confidence: 90%
“…The mean correlation coefficient for the inverse of serum cystatin C (1/serum cystatin C) from 36 data sets (R = 0.816, 95% CI = 0.804-0.826) ( 28 ) was much higher than that from the current study (R = 0.25). Similarly, Khorgami et al demonstrated the statistically significant correlation (P < 0.001) between serum cystatin C and simplified MDRD as well as cystatin C-based formula in chronic hemodialysis individuals with correlation coefficients of -0.46 and -0.87, respectively ( 29 ). This difference can be partially explained by the characteristics of patients.…”
Section: Discussionmentioning
confidence: 94%
“…Serum cystatin C has been proposed in this regard. [8][9][10][11][12][13] Cystatin C is a non-glycosylated protein of the cysteine proteinase inhibitors family that is produced by nearly all nucleated cells in the human body. 14,15 The production rate of this low molecular weight protein of 13 kDa is nearly constant, and is independent of age, sex, and body mass index(BMI).…”
Section: Introductionmentioning
confidence: 99%